Physical fitness of water lifeguards and the structure of a classical rescue operation - Kowalski, Damian; Skalski, Dariusz W.; Tsyhanovska, Nataliia; Grygus, Igor; Sydorko, Oleh (My University, 2025)
Background and Study Aim.Water-based leisure activities continue to grow in popularity, increasing the de-mand for effective water rescue services and placing high physical and technical requirements on lifeguards. Although existing systems of lifeguard training and certification widely use standardized tests of general physi-cal fitness and swimming performance, previous research indicates that such assessments may not adequately reflect the real demands of rescue operations. Water rescue ac-tions are complex motor tasks performed un-der conditions of fatigue, time pressure, and environmental resistance, requiring the integrated application of strength, endurance, speed, coordination, and technical skills. However, discrep-ancies persist between formal fitness evaluation criteria and actual professional requirements. Therefore, the aim of this study was to assess the relationship between general physical fitness indicators and performance in a task-specific rescue test simulating a classical water rescue operation without specialized equipment. The study sought to determine whether com-monly used fitness tests adequately predict lifeguards’ operational readiness.Material and methods.The study involved 100 certified and physically active lifeguards (54 females and 46 males) with professional experi-ence in water rescue. Participants voluntarily took part in a pedagogical experi-ment approved by an ethics committee. Anthropometric measurements were collected, including body height, body mass, and body mass index (BMI). General physical fitness was assessed using a 400 m freestyle swim-ming test and five selected EUROFIT tests evaluating flexi-bility, explosive power, muscular endurance, functional strength, and agility. In addition, an original comprehensive test was developed to simulate a classical rescue action, combining land-based exercises, swimming to a victim, victim con-trol and towing, evacuation to shore, and final physical effort. Descriptive statistics and correlation analyses were ap-plied to examine relationships between test outcomes.Results.The majority of participants achieved satisfactory results in general physical fitness tests and the 400 m swimming test. However, average completion times in the original rescue test exceeded the accepted perfor-mance norm for both fe-males and males. No strong correspondence was observed between passing standard fitness tests and successful per-formance in the task-specific rescue test. Positive relationships were identified between the shuttle run, the 400 m swimming test, and the original test (p < 0.05). Sex-related differences were observed, with females achieving better results in flexibility and agility, while males demonstrated higher absolute strength and faster average swimming times.Conclusions.The findings indicate that general physical fitness tests alone are insufficient to assess lifeguards’ readiness for real res-cue operations. Task-specific assessments that integrate multiple motor abilities provide a more valid evaluation of operational performance. The implementation of comprehensive rescue-oriented fitness tests may improve training effectiveness, certification quality, and long-term safety outcomes. Future research should focus on developing age- and sex-adjusted normative values and validating such tests in open water con-ditions.

Зростання популярності дозвілля у водному середовищі зумовлює підвищені вимоги до ефективності діяльності служб водного рятування та рівня професійної підготовленості рятувальників. Незважаючи на широке застосу-вання у системах підготовки та сертифікації стандартизованих тестів загальної фізичної підготовленості та плавальної працездатності, результати попередніх досліджень свідчать про обмежену відповідність таких оці-нювальних процедур реальним умовам проведення рятувальних операцій. Рятувальні дії на воді є складними руховими актами, що виконуються в умовах втоми, дефіциту часу та змінних факторів навколишнього середо-вища і потребують інтегрованого прояву сили, витривалості, швидкості, координації та спеціальних технічних умінь. У зв’язку з цим метою дослідження стало з’ясування взаємозв’язку між показниками загальної фізичної підготовленості та результативністю виконання спеціального комплексного тесту, що моделює класичну ряту-вальну операцію на воді без використання спеціального спорядження.
Keywords: рятування водне; фізична підготовка рятувальників; fitness; motor skills; rescue operation